2012
DOI: 10.1002/ab.21417
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Selective Exposure and the Enjoyment of Television Violence

Abstract: The existing research on the appeal of media violence has led to an apparent incongruity: violent content tends to increase selective exposure to media, but violence often decreases enjoyment. In this experiment, we used two independent manipulations to assess the role of violence in both selective exposure and enjoyment in order to examine the relationship between the two. Program descriptions for four prime-time television dramas were altered to create violent and nonviolent descriptions for each episode. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…A meta-analysis by Weaver (2011) based on 65 studies about the effects of violence on selective exposure and enjoyment confirmed that violent content increases exposure but decreases enjoyment in viewers. These findings were also confirmed experimentally (Weaver and Kobach 2012). In another experimental study, Stanca, Gui, and Gallucci (2013) found that when verbal violence is present in talk-shows, subjects watch more of a given program while reporting a significantly lower satisfaction level for the overall viewing experience.…”
Section: Physiological Attractionsupporting
confidence: 59%
“…A meta-analysis by Weaver (2011) based on 65 studies about the effects of violence on selective exposure and enjoyment confirmed that violent content increases exposure but decreases enjoyment in viewers. These findings were also confirmed experimentally (Weaver and Kobach 2012). In another experimental study, Stanca, Gui, and Gallucci (2013) found that when verbal violence is present in talk-shows, subjects watch more of a given program while reporting a significantly lower satisfaction level for the overall viewing experience.…”
Section: Physiological Attractionsupporting
confidence: 59%
“…In addition, another factor not accounted for in the present model has been suggested in a recent experimental study by Kobach and Weaver (2012). They found that pictures that were assumingly showing fictional violence triggered less negative affect in male participants (but not female participants) than the same pictures assumingly showing real violence.…”
Section: Unexpected Findings Unexplained Variance and Study Limitatmentioning
confidence: 83%
“…Baumeister et al (2007) argue that anticipatory emotions profoundly influence behaviour: ‘People learn to anticipate emotional outcomes and behave so as to pursue the emotions they prefer’ (p. 168). Accordingly, those who enjoy certain media content are more likely to use it than those who do not enjoy it (Zillmann, 1988; but also see Weaver and Kobach, 2012). Individuals that anticipate enjoyment when engaging in virtual violence should be more likely to approach violent video games, and individuals that anticipate regret, shame, guilt or disgust, more likely to avoid them.…”
Section: The Gender Gap In Violent Video Game Usementioning
confidence: 99%
“…Fictional devices, whether interactive or not, present the potential to forge cognitive representations alternative to the real world and the enaction of corresponding behaviours. [89,200] As it was observed in Orwell's War of the Worlds 1938 radio narration [158], in absence of alternative points of reference, fictional devices may succeed in presenting a credible version of reality, a simulation that might exclude or change the usual rationalisation processes.…”
Section: Fiction Primingmentioning
confidence: 99%